Perineal recurrence of prostate ductal adenocarcinoma after transperineal brachytherapy: a case report and literature review - Fukagai, Takashi; Hirayama, Kidai; Morita, Masashi; Nishimura, Kota; Yamatoya, Jin; Noguchi, Tetsuo; Ogawa, Yu; Igarashi, Atsushi; Morota, Madoka; Kato, Masako; Oshinomi, Kazuhiko; Ogawa, Yoshio; et al. (Journal of Contemporary Brachytherapy, 2020)
Perineal recurrence after brachytherapy is an exceedingly rare complication. Moreover, ductal adenocarcinoma is a rare histological variant of prostate cancer. Herein, we describe a case of perineal recurrence from ductal adenocarcinoma of prostate after low-dose-rate brachytherapy (LDR-BT) in a 65-year-old male patient. The patient had localized prostate cancer, for which he received LDR-BT; however, he experienced perineal recurrence 2 years after receiving LDR-BT. Surgical excision was attempted, but we were unable to remove the whole tumor, owing to invasion to surrounding tissue. Pathological examination of resected tumor showed ductal adenocarcinoma of the prostate. External beam radiation therapy and high-dose-rate brachytherapy (HDR-BT) were performed for residual tumor. Mild mediastinal lymph node swelling was observed during clinical course of the disease. Hence, androgen deprivation therapy was administered with abiraterone after radiation therapy, and prostate-specific antigen level decreased to undetectable level. Biochemical failure after transperineal brachytherapy for prostate cancer should be considered as a perineal recurrence.